2022
DOI: 10.1002/cctc.202200688
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ Investigations of Co@Al2O3 Ammonia Decomposition Catalysts: The Interaction between Support and Catalyst

Abstract: Cracking of ammonia, a hydrogen carrier with high storage capacity, gains increasing attention for fuel cell systems for heavy load transportation. In this work, we studied the influence of metal loading and synthesis temperatures on the properties of Co@Al2O3 catalysts. The combination of in situ bulk characterization methods with in situ surface spectroscopy provides insights into the structure‐property relation of the Co catalyst on the γ‐Al2O3 support. At too high temperatures, the formation of CoAl2O4 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Numerous metals, including Ru, Ir, Ni, Rh, Pt, Pd, Co, and Fe, have been demonstrated to act as catalysts for the breakdown of ammonia in earlier studies. Ru is well known for being the most effective catalyst in the group.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous metals, including Ru, Ir, Ni, Rh, Pt, Pd, Co, and Fe, have been demonstrated to act as catalysts for the breakdown of ammonia in earlier studies. Ru is well known for being the most effective catalyst in the group.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, no CO 2 or CO emissions are created during the decomposition of ammonia to produce hydrogen. The gas produced by this reaction is attractive as a fuel for fuel cells that operate at low temperatures, such as polymer electrolyte fuel cells (PEFCs) because the Pt electrode is easily poisoned by CO. 6,7 Numerous metals, including Ru, 8 Ir, 9 Ni, 10 Rh, 11 Pt, 12 Pd, 13 Co, 14 and Fe, 15 have been demonstrated to act as catalysts for the breakdown of ammonia in earlier studies. Ru is well known for being the most effective catalyst in the group.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interpretation of such data may be misleading. Weidenthaler et al reported the formation of cobalt aluminate species under reaction conditions that hinder the catalytic activity by a series of in situ XRD and XPS studies on Co/γ-Al 2 O 3 catalysts, highlighting the importance of in situ studies in revealing the true structure–property relationships …”
Section: Introductionmentioning
confidence: 99%
“…Weidenthaler et al reported the formation of cobalt aluminate species under reaction conditions that hinder the catalytic activity by a series of in situ XRD and XPS studies on Co/γ-Al 2 O 3 catalysts, highlighting the importance of in situ studies in revealing the true structure−property relationships. 33 In this work, the structure−property relationship of Ni catalysts supported on MgO for ammonia decomposition is discussed. The catalysts were synthesized by two different routes, wet impregnation (WI) and coprecipitation (CP), leading to different microstructures and properties such as reducibility to obtain the active species for ammonia decomposition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While noble metal Ru-based catalysts have been proven to de-compose NH3 completely at relatively low temperatures (~400-450 °C) [9][10][11][12], its high costs and scarcity present a hurdle in the commercial viability of NH3 as a hydrogen carrier [13][14][15]. Recent literature has thus focused on the development of non-noble metals such as Co [16,17], Ni [18,19], or Fe [20][21][22] as the major active components [23,24]. A common strategy for boosting these metals' performance is through synthesizing bi-or multi-metallic catalysts that mimic the ideal N-binding characteristic of Ru [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%